AMBIVALENSI KEKUASAAN PREROGATIF PRESIDEN PASCA AMANDEMEN KONSTITUSI - Laode Harjudin (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. This study discusses the political process relating to the issue of presidential prerogative control with an emphasis on the views and interests of the actors involved in discussing the issue. This study explains two main questions, namely how the actualization of presidential prerogative powers in Indonesia's presidential system after the constitutional amendment and what is behind the ambivalence of the president's prerogative power formulation in Indonesia's presidential system after the constitutional amendment. This study finds that constitutional amendments related to the president's prerogatives show ambivalence that distorts the prerogative meaning itself and is not strict between limiting or actually expanding the president's power. This happens because of the tug-of-war between legislative and executive interests. Behind the issue of controlling the president's prerogative powers, there is the interest of legislative institutions to equalize power with the president. Instead, the executive seeks to maintain or extend the president’s prerogative power.Keywords: Prerogative Power; Presidential; Amendment of Constitutions.Abstrak. Studi ini membahas proses politik berkaitan dengan isu pengendalian prerogatif presiden dengan penekanan pada pandangan dan kepentingan para aktor yang terlibat dalam pembahasan isu tersebut. Studi in menjelaskan dua pertanyaan pokok: (1) Bagaimana aktualisasi kekuasaan prerogatif presiden dalam sistem presidensial Indonesia pasca amandemen konstitusi? (2) Apa yang melatarbelakangi ambivalensi rumusan kekuasaan prerogatif presiden dalam sistem presidensial Indonesia pasca amandemen konstitusi? Hasil studi inii menemukan bahwa amandemen konstitusi terkait dengan prerogatif presiden menampakkan ambivalensi yang mendistorsi makna prerogatif itu sendiri dan tidak tegas antara membatasi atau justru memperluas kekuasaan presiden. Hal ini terjadi karena adanya tarik menarik antara kepentingan legislatif dan eksekutif. Di balik isu pengendalian kekuasaan prerogatif presiden, ada kepentingan institusi legislatif untuk menyetarakan kekuasaan dengan presiden. Sebaliknya, pihak eksekutif berupaya untuk mempertahankan atau mempeluas kekuasaan prerogatif presiden.Kata Kunci: Kekuasaan Prerogatif; Presidensial; Amandemen Konstitusi.